An exploratory study of Western firms’ failure in the Chinese market: a network theory perspective - Bilro, R.G.; Cunha, J. F. Da (Journal of Chinese Economic and Foreign Trade Studies, 2021)
Purpose – This paper aims to explore the external factors that lead Western firms to fail in the Chinese market, proposing to reveal the main challenges they face in this market, such as culture, guanxi or others. Based on network theory, the authors propose to group failure attributes and actions to predict business failure. Design/methodology/approach – Qualitative research based on in-depth interviews is conducted, with a sample of 21 individuals, from former/current managers that did or are currently doing business in China and a person from the Chinese Government. This research resorts to inductive reasoning and to Atlas.ti software to perform the analysis. Findings – The findings reveal that it is possible to cluster seven distinct categories of external factors. Additionally, Chinese culture, local partnerships and the “catching-up effect” by Chinese firms are also external factors to be considered. The role of guanxi in China is changing, taking another format, and international companies in the Chinese market must take this into account. Research limitations/implications – Several limitations arise in this research, such as information availability and time constraints, sample size and the characteristics of Chinese society (i.e. type of government). This study also proposes further confirmatory research to test the seven clusters proposed. Practical implications – Managers can understand patterns of business failures when targeting the Chinese market and use the seven clusters as a tool to address this market appropriately in the future. Originality/value – This paper intends to shed light on Western firms’ business failure in the Chinese market. The authors argue that several external factors linked to network surroundings contribute to Western firms failing in this market and that network failure attribution is still an understudied topic.